Global intellectual trend of Corpus linguistics studies among scholars in social sciences from September 2013 – September 2021 / Chen Minjie ... [et al.] - Minjie, Chen; Wong, Wei Lun; Guojie, Yin; Swaran Singh, Charanjit Kaur; Mihat, Warid; Yoong, Soo May (Universiti Teknologi MARA, 2023)
The primary objective of this article is to undertake a comprehensive and methodical examination of corpus-driven research endeavours carried out in the Asian region. A plethora of recent scholarly investigations have elucidated that the employment of corpus-driven methodologies across diverse fields and aims could derive advantageous outcomes through the utilisation of a diverse array of corpus linguistics software tools. The primary objective of corpus-driven analysis is to facilitate scholars in acquiring novel insights pertaining to a specific corpus, including the identification of pivotal keywords. The present investigation undertook a comprehensive examination of 21 scholarly research publications through the meticulous application of a systematic literature review methodology. The selection of Google Scholar and Scopus as the designated databases for the purpose of conducting a comprehensive search for pertinent scholarly resources has been made. A total of twelve research articles were procured from the Scopus database, whereas an additional eight articles were obtained from the esteemed Google Scholar platform. The empirical evidence presented in this study demonstrates the significance of corpus-driven research within the realm of Asian studies, primarily owing to the inherent ethnic diversity prevalent in this particular geographical region. The exploration of authentic language can be undertaken through a lens characterised by determination and focus. This statement elucidates the fact that the utilisation of corpus-driven research methodologies yields a greater abundance of relevant and genuine data, particularly within the realm of linguistics disciplines.